How Community Empowerment through Intellectual Property Protection of Traditional Knowledge Fosters Sustainable Innovation - Naik, Riti; Sreenivasulu, N.S. (Frontiers in Law, 2026)
Intellectual Property (IP) protection is presently the most common method of protection for Traditional Knowledge (TK) in mostly all countries. When any product, process, plant variety, biological resource etc. is accorded IP protection for e.g. under Geographical Indications or under Plant Varieties etc., not only one single creator but an entire community benefits from the protection. Community empowerment refers to the process of enabling communities to increase control over their lives whereby they alone can take life impacting decisions. Looking at communities who are rich in TK, the paper will attempt in drawing the link between how enabling IP protection for their TK can empower communities and make these groups more economically secure. Only laws in India have been used in this paper. A question then arises whether this entire process fosters innovation? IP has a definitive link with innovation. Works which seek IP protection often have to go through the initial test of novelty, originality or innovation. Looking at the difficulty of passing the test of novelty in the case of TK, talking about innovation in its case seems to be a farfetched idea. However, on the other hand a holistic approach to understand TK entails that any kind of protection of TK, whether it be through IP protection or legal protection or economically-benefitting schemes introduced by the government etc., is not exclusive from empowerment and community strength-building. And when the community flourishes, they will naturally create new methods to express themselves. This is likely to bring in innovation. Without innovation, a culture/community/tradition will eventually fade and die. This paper will argue that there is a mutual relationship between community empowerment through IP protection of TK and innovation.